International crime and justice - Natarajan, M.; Natarajan, Mangai (Cambridge ; New York : Cambridge University Press, 2011)
"International crime and justice is an emerging field that covers international and transnational crimes that have not been the focus of mainstream criminology or criminal justice. This book examines the field from a global perspective. It provides an introduction to the nature of international and transnational crimes and the theoretical perspectives that assist in understanding the relationship between social change and the waxing and waning of the crime opportunities resulting from globalization, migration, and culture conflicts. Written by a team of world experts, it examines the central role of victim rights in the development of legal frameworks for the prevention and control of transnational and international crimes. It also discusses the challenges to delivering justice and obtaining international cooperation in efforts to deter, detect, and respond to these crimes. This book is arranged in nine parts covering the subject matter of international criminal justice. Each of the short chapters provides readers with an understanding of the main concepts relevant to the topic and sensitizes them to the complex nature of the problems"--
48. The ICC processing of the Darfur Situation -- 49. Victims' rights in the International Criminal Court -- 50. NGOs and international criminal justice -- 51. Human rights commissions -- 52. The Truth and Reconciliation Commission in South Africa -- 53. The Guatemalan truth commission -- Part VII. International Cooperation and Criminal Justice: 54. World policing systems -- 55. Cross-border policing -- 56. Challenge and transition -- policing developments in the European criminal justice system -- 57. The European Union and judicial cooperation -- 58. The longer arm of the law: the growth and limits of international law enforcement and criminal justice cooperation -- 59. International co-operation to combat money laundering -- Part VIII. International Research and Crime Statistics: 60. National crime statistics: U.S. uniform crime reports and the National Crime Victimization Survey -- 61. Highlights of the International Crime Victims Survey -- 62. Cross-national comparisons based on official statistics of crime -- 63. International self-report delinquency -- 64. Qualitative comparative criminological research methods -- Part IX. International Research Resources: 65. International criminal justice: printed and electronic media, journals and professional associations -- 66. World criminal justice library network.
Includes bibliographical references and index.
Keywords: Transnational crime; Criminology -- Cross-cultural studies; Criminal justice, Administration of -- International cooperation; Criminal justice, Administration of -- Cross-cultural studies; Criminal justice, Administration of; Criminal justice, Administration of -- International cooperation; Criminology; Transnational crime; Cross-cultural studies